Modelling and Control of a Two-Wheel Inverted Pendulum Using Fuzzy-PID-Modified State Feedback - Karima Nader; Driss Sarsri (Journal of Robotics)
Control of mechanical systems by electronic systems controlled by computer programs is one of the most active research areas in mechatronic systems engineering. These programs carry out control laws, which are algorithms. This study focuses on Segway control (a two-wheeled inverted pendulum which is a highly nonlinear and unstable open-loop system). Our research entails creating a control law to stabilize this system. We proposed using a state feedback controller, which provided us with a stable system and a lower error margin; however, to correct this error, we used a combination of the state feedback controller and the fuzzy-PID controller. The effectiveness of the proposed method is demonstrated using simulation results.